Genetic background, recent advances in molecular biology, and development of novel therapy in Alport syndrome - Kandai Nozu; Yutaka Takaoka; Hirofumi Kai; Minoru Takasato; Kensuke Yabuuchi; Tomohiko Yamamura; Tomoko Horinouchi; Nana Sakakibara; Takeshi Ninchoji; China Nagano; Kazumoto Iijima (The Korean Society of Nephrology, 2020)
Alport syndrome (AS) is a progressive inherited kidney disease characterized by hearing loss and ocular abnormalities. There are three forms of AS depending on inheritance mode: X-linked Alport syndrome (XLAS), autosomal recessive AS (ARAS), and autosomal dominant AS (ADAS). XLAS is caused by pathogenic variants in COL4A5, which encodes type IV collagen α5 chain, while ADAS and ARAS are caused by variants in COL4A3 or COL4A4, which encode type IV collagen α3 or α4 chain, respectively. In male XLAS or ARAS cases, end-stage kidney disease (ESKD) develops around a median age of 20 to 30 years old, while female XLAS or ADAS cases develop ESKD around a median age of 60 to 70 years old. The diagnosis of AS is dependent on either genetic or pathological findings. However, determining the pathogenicity of the variants detected by gene tests can be difficult. Recently, we applied the following molecular investigation tools to determine pathogenicity: 1) in silico and in vitro trimer formation assay of α345 chains to assess triple helix formation ability, 2) kidney organoids constructed from patients' induced pluripotent stem cells to identify α5 chain expression on the glomerular basement membrane, and 3) in vitro splicing assay to detect aberrant splicing to determine the pathogenicity of variants. In this review article, we discuss the genetic background and novel assays for determining the pathogenicity of variants. We also discuss the current treatment approaches and introduce exon skipping therapy as one potential treatment option.